The length of a room exceeds its breadth by 3dm; if the length had been increased by 3dm, and the
breadth diminished by Adm, the area would not have been altered. Find the dimensions?
Answers
Answered by
0
Breadth of room =x
Length = x+3
A= x(x+3)
New length x+6
Breadth =x-4
Area (x+6)(x-4)
Therefore x(x+3)=x+6)(x-4)
3x=2x -24
X= -24 not feasible conditions
Length = x+3
A= x(x+3)
New length x+6
Breadth =x-4
Area (x+6)(x-4)
Therefore x(x+3)=x+6)(x-4)
3x=2x -24
X= -24 not feasible conditions
Similar questions